The Impact of Privatization on Minority Faith Prison Chaplains in Canada - Abdulkadir, Adar; Long, Ibrahim J. (2021)
Canadian federal prison chaplaincy underwent a major shift in 2013 when the provision of its services was privatized and outsourced to a single for-profit company. This article presents a summary of the experiences and concerns expressed by minority faith chaplains serving in federal correctional institutions following privatization. It is based on ten in-depth, semi-structured interviews with minority faith prison chaplains. The results show that minority faith federal prison chaplains are concerned about increased levels of bureaucratization that have compromised the quality of spiritual care available to prisoners, reductions in resources for chaplains, and increased levels of emotional exhaustion and frustration among themselves and fellow minority faith chaplains serving in Canadian correctional facilities.
Keywords: Minorities; Religion; Privatization; Prison; Chaplaincy